Lutein and Zeaxanthin Supplementation in Preterm Very Low-Birth-Weight Neonates in Neonatal Intensive Care Units: A Multicenter Randomized Controlled Trial - Manzoni, Paolo; Guardione, Roberta; Bonetti, Paolo; Priolo, Claudio; Maestri, Andrea; Mansoldo, Caterina; Mostert, Michael; Anselmetti, Giovanni; Sardei, Daniela; Bellettato, Massimo; Biban, Paolo; Farina, Daniele (American Journal of Perinatology, 2013)
Background Human milk feeding protects against oxidative stress-induced damage in preterm neonates, including severe multifactorial diseases such as retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC), and bronchopulmonary dysplasia (BPD). The carotenoids, which are not found in formula milk, might play a key role in these actions.Methods A multicenter, double-blind, randomized controlled trial was conducted in three tertiary Italian neonatal intensive care units. All preterm infants <32+6 weeks' gestational age were eligible and were randomized to a single, oral, daily 0.5-mL dose of carotenoid supplementation (0.14 mg lutein + 0.0006 mg zeaxanthin) or placebo (5% glucose solution) from birth till 36 weeks' corrected gestational age. Primary outcomes were threshold ROP, NEC > second stage, and BPD. Surveillance for detection of these diseases and for intolerance/adverse effects was performed.Results No treatment-related adverse effect was documented in the 229 analyzed infants, whose clinical/demographical characteristics were similar in the two groups. Threshold ROP incidence did not significantly differ in treated (6.2%) versus not treated infants (10.3%; p = 0.18). The same occurred for NEC (1.7% versus 5.1%; p = 0.15) and BPD (4.5% versus 10.3%; p = 0.07). Noteworthy, the progression rate from early ROP stages to threshold ROP was decreased by 50% (0.30 versus 0.44; p = 0.23).Conclusion Lutein/zeaxanthin supplementation in preterm infants is well tolerated. No significant effect was seen on threshold ROP, NEC, or BPD. The decreasing trends of these outcomes in the treatment group need to be assessed and confirmed on larger sample-sizes.
Keywords: nutrition; lutein; zeaxanthin; preterm neonates; ROP; BPD; NEC; prevention